Understanding what makes dark traits "vulnerable": A distinction between indifference and hostility. (1st July 2020) - Curtis, Shelby R.; Jones, Daniel N.
Abstract: The Dark Triad of personality is comprised of three callous and manipulative traits: psychopathy, Machiavellianism, and narcissism (Paulhus & Williams, 2002). A complementary "Vulnerable" Dark Triad accounts for heterogeneity within these traits: secondary psychopathy, borderline personality disorder, and vulnerable narcissism (Miller et al., 2010). Based in theory suggesting differences in the underlying motives of these distinct triads, we conducted a study to investigate whether motive differences are due to distinct aspects of antagonism. Specifically, we hypothesized that people high in the Dark Triad are interpersonally driven by extrinsic motives due to an indifferent interpersonal core. We also hypothesized that people high in the Vulnerable Dark Triad are interpersonally driven by intrinsic motives due to a hostile interpersonal core. The hypothesis regarding the Dark Triad was partially supported, such that individuals high in the Dark Triad core reported pursuing extrinsic motives, and this relationship is partially mediated by a lack of honesty/humility. However, there were no differences in motive pursuit between the two triads. Additional empirical research should more formally investigate the distinctions between the Dark Triad and its vulnerable counterpart.